UNIversity students' LIFEstyle behaviours and Mental health cohort (UNILIFE-M): study protocol of a multicentre, prospective cohort study - Schuch, Felipe B.; Waclawoscky, Aline; Tornquist, Debora; Oyeyemi, Adewale L.; Sadarangani, Kabir P.; Takano, Keisuke; Teychenne, Megan; Balanzá-Martínez, Vicent; O'Neil, Adrienne; Romain, A. J.; McGrath, Aisling; Alselmi, Alejandro; et al. (BMJ Open, 2026)
INTRODUCTION: Students enrolling in higher education often adopt lifestyles linked to worse mental health, potentially contributing to the peak age onset of mental health problems in early adulthood. However, extensive research is limited by focusing on single lifestyle behaviours, including single time points, within limited cultural contexts, and focusing on a limited set of mental health symptoms. METHODS AND ANALYSIS: The UNIversity students' LIFEstyle behaviours and Mental health cohort (UNILIFE-M) is a prospective worldwide cohort study aiming to investigate the associations between students' lifestyle behaviours and mental health symptoms during their college years. The UNILIFE-M will gather self-reported data through an online survey on mental health symptoms (ie, depression, anxiety, mania, sleep problems, substance abuse, inattention/hyperactivity and obsessive/compulsive thoughts/behaviours) and lifestyle behaviours (ie, diet, physical activity, substance use, stress management, social support, restorative sleep, environment and sedentary behaviour) over 3.5 years. Participants of 69 universities from 28 countries (300 per site) will be assessed at university admission in the 2023 and/or the 2024 academic year and followed up for 1, 2 and 3.5 years. ETHICS AND DISSEMINATION: The study was first approved at a national level in Brazil (CAE:63025822.8.1001.5346). Study sites outside Brazil obtained additional ethics approval from their institutions using the main approval. Results from the UNILIFE-M cohort will be disseminated through scientific publications, presentations at scientific meetings, press releases, the general media and social media.
CRIS-Team Scopus Importer:2026-01-23
Keywords: Behavior; Health; MENTAL HEALTH